[RETRACTED] Analisis Metakognisi Peserta Didik dalam Pemecahan Masalah pada Materi Turunan (Kreano, Jurnal Matematika Kreatif-Inovatif, 2018)
[THIS ARTICLE HAS BEEN RETRACTED]Following a rigorous, carefully concerns and considered review of the article published in Kreano, Jurnal Matematika Kreatif-Inovatif to article entitled â€œAnalisis Metakognisi Peserta Didik dalam Pemecahan Masalah pada Materi Turunanâ€ Vol 9, No 1, pp. 84-92, Juni 2018, DOI: 10.15294/kreano.v9i1.13125.The document and its content has been removed from Kreano, Jurnal Matematika Kreatif-Inovatif, and reasonable effort should be made to remove all references to this article.